Business Process Improvement Sistem Pelayanan Klinik Promec Menggunakan Metode Time Motion Study and Value Stream Mapping Untuk Mengurangi End-To-End Lead Times - Fransiska Mochtar; Purwadhi Purwadhi; Nining Handayani (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
Process efficiency is a key factor in improving the quality of healthcare services, especially in outpatient facilities such as clinics. This study presents a case study at Promec Clinic in Jakarta, aiming to identify bottlenecks and design process improvement recommendations to reduce end-to-end lead time. A descriptive and explanatory quantitative approach was employed, integrating Time and Motion Study (TMS) and Value Stream Mapping (VSM) as primary analysis tools. Data were collected through direct observation of 100 patients, interviews with staff, and operational process satisfaction questionnaires. The results indicate that the